Intraspecific variations and additional information about Cheletomimus (Hemicheyletia) wellsi (Baker, 1949) (Trombidiformes: Cheyletidae) from Brazil - Bizarro, Gabriel; da Silva, Guilherme L.; Silva, Rita T. L.; Ueckermann, Edward A.; Ferla, Noeli J.; Johann, Liana (Entomological Communications, 2021)
In this paper, we presented additional information to the description of Cheletomimus (Hemicheyletia) wellsi (Baker, 1949) (Acari: Cheyletidae) collected on Vitis vinifera L. (Vitaceae), Ruellia angustiflora (Ness) Lindau ex Rambo (Acanthaceae) from Dois Lajeados, Marques de Souza and Pantano Grande municipalities in Rio Grande do Sul state, and on Malus domestica Borkh (Rosaceae) in Campo do Tenente municipality, Paraná state, Brazil. The specimens examined presented intraspecific variations from those described previously. These variations will be discussed herein. A key to the known Brazilian species of the genus is provided.